TATA KELOLA DESA MEKARSARI DAN PENGEMBANGAN EKONOMI KERAJINAN BAMBU BERBASIS CONTINUOUS IMPROVEMENT DAN ADMINISTRASI PEMBANGUNAN DESA - Lukman Nulmunir; Yusup Musyaffa; Gugun Geusan Akbar; Ike kania (Department of Public Administration, Faculty of Social and Political Science, Universitas, 2026)
Village economic development is a strategic effort to improve community welfare by utilizing local potential. Mekarsari Village has the potential to develop bamboo crafts as a basis for the village's creative economy, but its development still faces various obstacles, such as limited village governance, weak development administration, and low-quality production and marketing systems. This study aims to analyze the role of village governance, the application of the concept of continuous improvement, and village development administration in supporting the development of the bamboo craft economy in Mekarsari Village. The study used a descriptive qualitative approach with a case study method. Data collection was conducted through in-depth interviews, field observations, and documentation. The results indicate that the implementation of continuous improvement contributes to improving product quality, encouraging design innovation, and strengthening community business institutions. Furthermore, integrated village development administration through planning, budgeting, and monitoring can support the sustainability of village economic development programs. The synergy between good village governance, continuous improvement, and effective development administration has the potential to strengthen bamboo craft development and enhance local economic resilience in a sustainable manner.